DEVELOPMENT STRATEGY OF BEEF CATTLE IN SMALL SCALE BUSINESS AT WURYANTORO SUBDISTRICT OF WONOGIRI REGENCY - Sutrisno Hadi Purnomo; Endang Tri Rahayu; Sidiq Budi Antoro (Buletin Peternakan, 2017)
This study was aimed to determine the principal factors that may affect any development of the cattle business and know what strategies can be applied in the development of the cattle business in the District WuryantoroWonogiri. Research method used in this study was a mixed method collect qualitative and quantitative primary data from respondents and secondary data from relevant agencies, namely BPS Wonogiri, Wonogiri District Agriculture Office, and Subdistrict Wuryantoro. Research sampling was determined by convenience sampling of 60 farmers, and 10 respondents from public government and cattle traders. Analysis of data using internal and external situation analysis, also SWOT analysis. SWOT analysis qualitative of internal factors resulted in the identification of Strength and Weakness contained in the cattle business that consists of human resources, financial condition, operations / production, management, marketing. The analysis of external factors resulted in the identification of factors external in the form of opportunity and threats that exist in the beef cattle business as consisting of social, economic, public policy, and technology. The results of the matrix analysis showed results that the internal factors of 1.09 (on the x-axis), and external factors of 0.23 (on the y-axis).Hence,appropriate strategy in the development of beef cattle farms was in quadrant I that support aggressive growth policy (GrowthOriented Strategy),which uses strength to gain opportunities, profits in the cattle business.